Primeros registros del tigrillo Leopardus pardalis (Carnivora, Felidae) en el Santuario Histórico de Machupicchu, Cusco, Perú - Zarate-Pantoja, Yanira (2024)
We report for the first time the presence of the ocelot (Leopardus pardalis), in the Machupicchu Historic Sanctuary, using camera traps. Twenty-one independent photographic records were obtained in four montane forest sectors between June 2018 and March 2020. The altitudinal range recorded for this species within the Sanctuary ranges from 2193 to 3414 m of altitude, which includes the second highest elevation record in Peru. The records indicate a pattern of cathemeral activity, with no time preference between day and night, and suggest that the presence of ocelots in some areas above 3000 m may be more common than previously thought, with specimens present year-round.